Genetic Variants of Butyrylcholinesterase and Their Potential Impact on Human Health: A Narrative Literature Review - Bharmatisna Anggaharsya Nugraha (HM Publisher, 2021)
Butyrylcholinesterase (BChE) is an enzyme found in plasma and many other parts of the body. It is an enzyme that hydrolyses drugs containing ester bonds, such as drugs acting at the neuromuscular junction and local anaesthetic agent. This literature review aimed to describe genetic variants of butyrylcholinesterase. BChE polymorphisms have been shown to produce enzymes with varying levels of catalytic activity. Analysis of butyrylcholinesterase involves the determination of both enzyme activity and biochemical phenotypes. Phenotype is determined by the use of specific enzyme inhibitors (such as dibucaine or fluoride) that produce phenotype-specific patterns of dibucaine or fluoride numbers. Molecular genetic analyses can determine the true genotypes. In conclusion, genetic variants of human butyrylcholinesterase were one of the first examples in the new field of pharmacogenetics when it was recognized that abnormal response to succinylcholine was due to a mutated enzyme with low binding affinity.